Pengaruh Pendidikan Kesehatan E-Booklet pada Pengetahuan dan Sikap Orang Tua terhadap Vaksin Pneumococcal Conjugate Vaccine (PCV) dan Rotavirus Pentavalent (RV) di Posyandu Karangpucung - Fathiyyah Deka Argadaninggar; Deisy Sri Hardini (Universitas Malahayati, 2026)
ABSTRACT Diarrheal diseases and lower respiratory tract infections are significant factors contribuing to the reduction of life expectancy in children by 1.97 years and 2.09 years, respectively. In response, the government has included PCV and RV vaccines in the national immunization program. Parental knowledge and attitudes toward the PCV and RV vaccines are crucial for the success of the vaccination program in children. To analyze the impact of E-Booklet health education on parents’ knowledge and attitudes regarding the acceptance of PCV and RV vaccines. This study employed a quantitative quasi-eksperimental design with a one-group pretest-posttest approach. Data were collected using a questionnaire. The study involved 55 mothers with children aged 0-1 years, selected using proportionate stratified random sampling. The collected data were statistically processed using paired t-test analysis. The analysis revealed that parents' knowledge increased from an average score of 62.61 to 77.30, and their attitudes improved from an average score of 35.87 to 39.42. The Paired T-Test results showed a p-value of 0.000 0.05. There is a significant impact of the E-Booklet on the knowledge and attitudes of mothers regarding the PCV and RV vaccines at Posyandu (Integrated Health SeRVices) Karangpucung, as indicated by a p-value of 0.000. Keywords: PCV Vaccine, RV Vaccine, E-Booklet Educational Media. ABSTRAK Penyakit diare dan infeksi saluran pernapasan bawah menjadi faktor yang menyebabkan angka harapan hidup pada anak menurun hingga 1,97 tahun dan 2,09 tahun. Berkenaan hal tersebut pemerintah menjadikan imunisasi PCV dan RV ke dalam imunisasi nasional. Pengetahuan dan sikap orang tua mengenai vaksin PCV dan RV sangat penting dalam mendukung keberhasilan program vaksin pada anak. Menganalisis pengaruh pendidikan kesehatan E-Booklet terhadap pengetahuan dan sikap orang tua dalam penerimaan vaksin PCV dan RV. Jenis penelitian ini merupakan kuantitatif quasi ekserimental dengan rancangan one group pretest-postest design. Pengumpulan data dilakukan dengan menggunakan kuisioner. Jumlah responden sebanyak 55 ibu yang memiliki anak 0-1 tahun dengan teknik proportionate stratified random sampling. Data yang diperoleh kemudian diolah secara statistik menggunakan analisa uji paired t test. Hasil analisa diperolah pengetahuan orang tua yang semula rata-rata 62,61 menjadi 77,30 dan sikap orang tua yang semula rata-ratanya 35,87 menjadi 39,42. Hasil uji Paired T Test diperoleh nilai p-value 0,000 0,05. Terdapat pengaruh signifikan sebelum dan sesudah diberikan media E-Booklet terhadap pengetahuan dan sikap ibu mengenai vaksin PCV dan RV di Posyandu Karangpucung dengan nilai p-value 0,000. Kata Kunci: PCV Vaccine, RV Vaccine, E-Booklet Educational Media.